2019
DOI: 10.11159/icgre19.110
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Shear Strength Behavior of Soils Under Low Confining Pressure

Abstract: Mechanical behavior of soils is highly dependent on their composition. In order to gain better understanding of change in strength parameters according to soil composition, direct shear tests were conducted in this study. Sand was selected as preliminary soil type. Fine grained soil was mixed with sand step by step. Amount of fine grains was increased 10% in each step. Eleven different mixtures were obtained and standard proctor tests were conducted to determine highest unit weight and optimum water content fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Very few results are available in the literature on direct shear tests performed on reconstituted sand-clay mixtures in the laboratory [39,42,50,60,73,175,176]. Furthermore, the results do not provide a comprehensive understanding on the mechanical behavior of the sand-clay mixtures even though they clearly indicate that the clay content affects the shear behavior of the mixtures.…”
Section: Interface Direct Shear Tests On Sand-clay Mixturementioning
confidence: 98%
See 1 more Smart Citation
“…Very few results are available in the literature on direct shear tests performed on reconstituted sand-clay mixtures in the laboratory [39,42,50,60,73,175,176]. Furthermore, the results do not provide a comprehensive understanding on the mechanical behavior of the sand-clay mixtures even though they clearly indicate that the clay content affects the shear behavior of the mixtures.…”
Section: Interface Direct Shear Tests On Sand-clay Mixturementioning
confidence: 98%
“…The direct shear test is of significant importance to study the mechanical response of sand-clay mixture [39,42,60,73]. Direct shear tests were performed on the mixture of dry Ottawa sand and kaolinite clay by Vallejo and Mawby [42] to determine how the shear strength is influenced by the sand (or clay) fractions.…”
Section: • Direct Shear Testsmentioning
confidence: 99%
“…Few recent studies are found to investigate the physical and mechanical properties of sand with fines. The fines content improves dry density, shear strength, and reduce angle of internal friction (ϕ) up to a threshold of fines content [14,19,20]. The internal friction angle decreases with increase in fine content and cohesion increases [6,19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The fines content improves dry density, shear strength, and reduce angle of internal friction (ϕ) up to a threshold of fines content [14,19,20]. The internal friction angle decreases with increase in fine content and cohesion increases [6,19,21,22]. The undrained shear strength, soil modulus, and pore pressure decreased when the clay content increased [23].…”
Section: Introductionmentioning
confidence: 99%
“…Soils are found in composite form due to their formation process. Mechanical behaviour of soil such as shear strength, compressibility, erodibility, permeability are dependent on composition of soil [2]. Many investigations were conducted to acquire a comprehensive insight on the behaviour of soil mixtures [1][2] [3][4] [11] [14].…”
mentioning
confidence: 99%